2022
DOI: 10.3390/ma15165503
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Prediction of the Effect of Laser Shock Peening on Residual Stress and Fatigue Life of Ti-6Al-4V Titanium Alloy

Abstract: Laser shock peening (LSP) is a promising surface strengthening technology to improve the fatigue life of alloy components. In this work, the residual stress field of Ti-6Al-4V titanium alloy induced by LSP was simulated based on finite element method (FEM), and then the fatigue lives of the non-LSP and LSP-treated specimens subjected to four-point bending were predicted using the software Fe-safe. The simulation results were compared and validated with the corresponding experimental results. LSP treatment prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…However, a recent research article reported a significant difference in the experimental and fatigue results of Ti-6Al-4V alloy. The author claims that disregarding surface properties in the simulation is the reason for the difference [195]. Hence, simulation considering all the physical phenomena related to peening has to be developed to increase the reliability of the simulation.…”
Section: Challenges and Future Aspectsmentioning
confidence: 99%
“…However, a recent research article reported a significant difference in the experimental and fatigue results of Ti-6Al-4V alloy. The author claims that disregarding surface properties in the simulation is the reason for the difference [195]. Hence, simulation considering all the physical phenomena related to peening has to be developed to increase the reliability of the simulation.…”
Section: Challenges and Future Aspectsmentioning
confidence: 99%
“…At the same time, many new or novel laser processing technologies utilizing laser are emerged, and these processing technologies have brought great changes to the engineering fields. Laser shock processing (LSP) is a novel mechanical surface-strengthening technology with excellent strengthening effect, controllability, and adaptability [7,8,19,20]. Compared with the common mechanical surface supporting technologies such as SP, URSS, USP and WJP, the adequate beneficial compressive residual stress layer depth induced by LSP treatment can reach over 1 mm.…”
Section: Introductionmentioning
confidence: 99%
“…For gas turbines, the size of the impact object is usually on a millimeter scale, and the residual stress generated by the impact is not easy to measure in practice. Therefore, the use of an FOD numerical simulation method can be useful, as it can effectively describe the size and distribution of stress concentration [ 7 ], which is an effective method of studying the FOD damage law.…”
Section: Introductionmentioning
confidence: 99%